Loss of ARID1A Expression Is an Early Molecular Event in Tumor Progression From Ovarian Endometriotic Cyst to Clear Cell and Endometrioid Carcinoma. Issue 8 (1st October 2012) - Ayhan, Ayse; Mao, Tsui-Lien; Seckin, Tamer; Wu, Chen-Hsuan; Guan, Bin; Ogawa, Hiroshi; Futagami, Masayuki; Mizukami, Hiroki; Yokoyama, Yoshihito; Kurman, Robert J.; Shih, Ie-Ming
Abstract : Objectives: ARID1A is a recently identified tumor suppressor participating in chromatin remodeling. Somatic inactivating mutations of ARID1A and loss of its expression occur frequently in ovarian clear cell and endometrioid carcinomas and in uterine endometrioid carcinomas. Because endometriotic epithelium is thought to be the cell of origin of most ovarian clear cell and endometrioid carcinomas, we undertook an analysis of ARID1A expression of these tumors arising within an endometriotic cyst (endometrioma). Materials and Methods: Our immunohistochemical study set consisted of 47 endometriotic cysts containing clear cell carcinoma in 24 cases, well-differentiated ovarian endometrioid carcinoma in 20 cases, and mixed clear cell and endometrioid carcinoma in 3 cases. Results: ARID1A loss was observed in 31 (66%) of 47 carcinomas; and therefore, these cases were informative for determining the temporal sequence of loss of ARID1A expression in tumor progression. In 16 of the 47 cases, ARID1A immunoreactivity was retained in both the endometriotic cyst and the carcinoma; and thus, these cases were not informative. All of the 31 informative cases showed loss of ARID1A immunoreactivity in the carcinoma and in the endometriotic cyst epithelium in direct continuity with the carcinoma but not in the cyst epithelium that was not adjacent to the tumor. Conclusions: Loss of ARID1A function as shown by loss of expression, presumably due to mutations, is an early molecular event in the development of most ovarian clear cell and endometrioid carcinomas arising in endometriomas.